High-efficiency, wide-input-supply oscillator for switched capacitor converter in CMOS technology - Tan, Mun Bin (2023)

(untitled)
In this project, a voltage-controlled ring oscillator (VCRO) cross-coupled charge pump (CCCP) is proposed. The design of the VCRO is investigated to develop a high-performance oscillator to drive a CCCP. The project is conducted via Cadence Virtuoso software and the circuit is designed using 0.18μm CMOS technology with supply voltage of 3.3V. A VCRO with high frequency ranges from 227.10Mhz to 2428.71MHz is developed. In addition, a CCCP is incorporated with the VCRO to achieve a maximum efficiency of 89.07%. The outcomes of the simulation reveal the better performance of the proposed design as compared to the previous studies in terms of oscillation frequency for VCRO and efficiency for CCCP. The proposed VCRO-CCCP can be utilized for fast charge up application such as supercapacitor-based energy storage system and stable charging for portable electronic device in particular, mobile phones.